A panel of recombinant proteins from human‑infective Plasmodium species for serological surveillance - Nicole, Müller‑Sienerth; Shilts, Jarrod; Khamisah, Abdul Kadir; Yman, Victor; Homann, Manijeh Vafa; Muhammad, Asghar; Ngasala, Billy; Balbir, Singh; Färnert, Anna; Wright, Gavin J. (BMC, 2020)
Background